Peran Blogger dalam Meningkatkan Branding dan Penjualan Produk Rendang UMKM Mama Uci - Adi Kurniawan; Fauzan Anshari; Nova Dilastri; Sularno Sularno (CV. ITTC INDONESIA, 2025)
In today’s digital era, utilizing online media has become a crucial strategy for SMEs to expand their market reach and increase sales. This study examines the role of bloggers in enhancing branding and sales of Rendang products from the SME Mama Uci. The method used is a qualitative study involving interviews and observations of bloggers and SME actors. The results indicate that bloggers are effective in building brand image through informative and engaging content, thereby increasing consumer trust and expanding the market for Mama Uci’s Rendang products. Collaboration with bloggers also significantly contributes to increased sales volume. This study concludes that bloggers are strategic partners in digital marketing efforts for SMEs to improve competitiveness and business sustainability